2019
DOI: 10.1002/jmri.26944
|View full text |Cite
|
Sign up to set email alerts
|

Human Placenta Blood Flow During Early Gestation With Pseudocontinuous Arterial Spin Labeling MRI

Abstract: Background Noninvasive measurement of placental blood flow is the major technical challenge for predicting ischemic placenta (IPD). Pseudocontinuous arterial spin labeling (pCASL) MRI was recently shown to be promising, but the potential value in predicting the subsequence development of IPD is not known. Purpose To derive global and regional placental blood flow parameters from longitudinal measurements of pCASL MRI and to assess the associations between perfusion‐related parameters and IPD. Study Type Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Thus far, few studies have investigated the relation between perfusion and GA, showing opposite trends in normal 20,39 and abnormal 19 pregnancies. Recently, Liu et al showed perfusion‐related image parameters for ischemic placental disease were significantly decreased from normal pregnancy during early gestation 40 . The relation between perfusion and GA in women with normal and abnormal pregnancies should be further investigated in future studies with larger subject numbers.…”
Section: Discussionmentioning
confidence: 97%
“…Thus far, few studies have investigated the relation between perfusion and GA, showing opposite trends in normal 20,39 and abnormal 19 pregnancies. Recently, Liu et al showed perfusion‐related image parameters for ischemic placental disease were significantly decreased from normal pregnancy during early gestation 40 . The relation between perfusion and GA in women with normal and abnormal pregnancies should be further investigated in future studies with larger subject numbers.…”
Section: Discussionmentioning
confidence: 97%
“…Magnetic resonance imaging (MRI) is currently indicated in certain maternal conditions such as appendicitis, pulmonary embolism, renal colic, and trauma and provides excellent prospects for translational research 2 6 . MRI of hypoperfusion has been shown to be a marker of intrauterine growth restriction 7 and recent advances in pulse sequence design may enable a broader dissemination of placental perfusion MRI for clinical studies and diagnosis 8 . MRI was also successfully applied to investigate pregnancy in rodent models including dynamic contrast-enhanced MRI 9 11 , arterial spin labeling of placental perfusion 12 , diffusion MR of placental compartmental flow dynamics 13 , or blood/tissue oxygen level dependent (BOLD/TOLD) MRI of hemoglobin oxygenation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…MRI is a promising technique for fetal and placental imaging because it provides excellent soft-tissue contrast, functional imaging, and no ionizing radiation [ 7 , 8 ]. However, motion in the uterus during MRI still remains one of the major limiting factors for functional placenta and fetal imaging [ 9 , 10 ] as MRI is sensitive to motion artifacts due to a long acquisition time. To date, there is a limited understanding of the uterine motion, particularly in early gestation, and characterization of the uterine motion would be important to allow developing strategies to minimize motion-related MRI artifacts.…”
Section: Introductionmentioning
confidence: 99%